Comparison of Saffron versus Fluoxetine in Treatment of Mild to Moderate Postpartum Depression: A Double-Blind, Randomized Clinical Trial - Kashani, L.; Eslatmanesh, S.; Saedi, N.; Niroomand, N.; Ebrahimi, M.; Hosseinian, M.; Foroughifar, T.; Salimi, S.; Akhondzadeh, S. (Pharmacopsychiatry, 2017)
Introduction: Postpartum depression is a common mental health problem that is associated with maternal suffering. The aim of this double-blind clinical trial was to compare safety and efficacy of saffron and fluoxetine in treatment of mild to moderate postpartum depression.Methods: This was a 6-week, double-blind, randomized clinical trial. Subjects were women aged 18–45 years with mild to moderate postpartum depression who had Hamilton Depression Rating Scale (HDRS 17-item) score≤18. Eligible participants were randomized to receive either a capsule of saffron (15 mg capsule) or fluoxetine (20 mg capsule) twice daily for 6 weeks. The primary outcome measure was to evaluate efficacy of saffron compared to fluoxetine in improving depressive symptoms (HDRS score).Results: There was no significant effect for time×treatment interaction on HDRS score [F (4.90, 292.50)=1.04, p=0.37] between the 2 groups. 13 (40.60%) patients in the saffron group experienced complete response (≥50% reduction in HDRS score) compared with 16 (50%) in the fluoxetine group and the difference between the 2 groups was not significant in this regard (p=0.61). Frequency of adverse events was not significantly different between the treatment groups.Discussion: The results of this study may suggest that saffron is a safe alternative medication for improving depressive symptoms of postpartum depression. Nevertheless, it should be mentioned that the trial is not well powered and should be considered a preliminary study. Therefore, large clinical trials with longer treatment periods and comparison with placebo group would be appropriate for future studies.
Keywords: crocus sativus; fluoxetine; postpartum depression; saffron; SSRI